2014
DOI: 10.4102/sajbm.v45i3.130
|View full text |Cite
|
Sign up to set email alerts
|

Choosing celebrity endorsers for advertising campaigns in cosmopolitan China: Does their ethnicity matter?

Abstract: This study asks if endorsers function as surrogates for country-of-origin, and if the effectiveness of the tactic varies with the perceived ethnicity (Western versus Chinese) of the celebrities. It finds no significant influence on the country-oforigin perception, brand attitudes or product quality evaluations in the reactions of 797 consumers in Shanghai to magazine advertisements featuring celebrities of Chinese vs. Western ethnicity. The lack of any significant effect of the ethnicity of celebrities on a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…The result indicates that for participants from the same ethnic group as their supervisor, the relationship between IM and job satisfaction was stronger than that from different ethnic groups as their supervisor. This means that the preferential treatment given to those from the same ethnic group as their supervisor signals that although IM may be provided by the organisation, the actual realisation would be tilted towards the in-group members (Apaolaza, Hartman, He, Barrutia, & Echebarria, 2014;Urban, 2011). That IM interacted with ethnic similarity is not surprising because ethnic similarity plays out in the IM in organisations with those from similar ethnic groups as their supervisors getting most of the mobility (Egwa, 2016;Takyi-Asiedu, 1993).…”
Section: Discussion Outline Of Resultsmentioning
confidence: 99%
“…The result indicates that for participants from the same ethnic group as their supervisor, the relationship between IM and job satisfaction was stronger than that from different ethnic groups as their supervisor. This means that the preferential treatment given to those from the same ethnic group as their supervisor signals that although IM may be provided by the organisation, the actual realisation would be tilted towards the in-group members (Apaolaza, Hartman, He, Barrutia, & Echebarria, 2014;Urban, 2011). That IM interacted with ethnic similarity is not surprising because ethnic similarity plays out in the IM in organisations with those from similar ethnic groups as their supervisors getting most of the mobility (Egwa, 2016;Takyi-Asiedu, 1993).…”
Section: Discussion Outline Of Resultsmentioning
confidence: 99%
“…This is because the country of origin could be an indicator of quality and acceptability (Baughn and Yaprak, 1993;Zhou et al, 2002), whereas a Western country is usually connected with notions of success, status and modernity (Cheong et al, 2010;Zhou and Belk, 2004). However, a recent study by Apaolaza et al (2014) suggests that there is no relationship between the ethnicity of endorsers in advertising and the perceived countries of origin of endorsed brands, particularly in China's more cosmopolitan cities. Therefore, the effect of endorser ethnicity in international brand advertising may be modulated by other factors, such as how the endorser is portrayed, which has been overlooked in the existing literature.…”
Section: Endorser Ethnicitymentioning
confidence: 99%
“…In the literature of celebrity endorsement, there are mixed results regarding the impact of racial homophily. While some studies found that endorsers who matched the customer's ethnicity were found to be more persuasive (Erba et al, 2019; Hesapci et al, 2016), others reported that race of endorsers did not have any insignificant impact on customers' attitudes and perception (Apaolaza et al, 2014; Bui, 2017). However, Lord et al (2019) provide further insights on how that racial homophily influences customers' evaluation of endorsers' attractiveness and trustworthiness in different behavioral contexts, the study findings showed than racial homophily is particularly impactful in contexts of simpler consumer decision‐making, rather than in situations involving high‐involvement information processing.…”
Section: Literature Reviewmentioning
confidence: 99%